2000
DOI: 10.1161/01.cir.102.16.1977
|View full text |Cite
|
Sign up to set email alerts
|

Na + /H + Exchange Inhibitor Cariporide Attenuates Cell Injury Predominantly During Ischemia and Not at Onset of Reperfusion in Porcine Hearts With Low Residual Blood Flow

Abstract: Background-This study investigated whether myocardial protection by inhibition of Na ϩ /H ϩ exchange (NHE) occurs during ischemia and/or during reperfusion. Methods and Results-The left anterior descending coronary artery was occluded in 32 pigs for 60 minutes and then reperfused for 24 hours. Infarct sizes (nitroblue tetrazolium [NBT] stain, histology) were determined at the end of the experiments. An extracorporeal bypass was used to achieve a constant residual blood flow of 3 mL/min in the myocardium at ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 26 publications
4
39
0
2
Order By: Relevance
“…The protective effect of cariporide against cell death secondary to ischemiareperfusion was, therefore, fully explained in this model by its effect on ATP decay during the ischemic period. This result is consistent with previous studies showing that cariporide needs to be present during the ischemic period to be protective (6,16).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The protective effect of cariporide against cell death secondary to ischemiareperfusion was, therefore, fully explained in this model by its effect on ATP decay during the ischemic period. This result is consistent with previous studies showing that cariporide needs to be present during the ischemic period to be protective (6,16).…”
Section: Discussionsupporting
confidence: 93%
“…In a recent study (31), pretreatment with the selective NHE inhibitor SM-20550 was associated with attenuated Ca 2ϩ overload in mitochondria obtained from rat hearts submitted to 40 min of ischemia and 20 min of reperfusion, a result in agreement with the protective effect of NHE inhibition against cell necrosis secondary to ischemia-reperfusion, but [Ca 2ϩ ] m during ischemia was not measured. Our observation that cariporide, at concentrations that have been consistently found cardioprotective in isolated cells (25,27) and intact myocardium in vivo (6,16), enhanced mitochondrial Ca 2ϩ accumulation during simulated ischemia may appear surprising. Although increased [Ca 2ϩ ] m has been shown to have detrimental effects (4), there is a lack of information on the consequences of mitochondrial Ca 2ϩ overload during ischemia.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…injury in various tissues (20,36,47), we assessed the role of the basolaterally expressed NHE1 in the ischemia-injured ileum. However, blockade of NHE1 in the ischemia-injured mucosa with serosal application of the selective NHE1 inhibitors HOE-694 (25 M) or HOE-642 (cariporide, 25 M) had no effect on the recovery of TER, suggesting that NHE1 is not directly involved in mucosal barrier repair in this model.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies (20,36,47) that have reported protective properties of NHE1 inhibitors in ischemiareperfusion-injured porcine cardiac myocytes. In our intestinal ischemia model, inhibition of NHE2 appears to be responsible for the repair of ischemia-injured tissue.…”
Section: Blockade Of Apical Namentioning
confidence: 99%